2016
DOI: 10.1103/physrevb.93.245431
|View full text |Cite
|
Sign up to set email alerts
|

Space charges and defect concentration profiles at complex oxide interfaces

Abstract: We discuss electronic and ionic defect concentration profiles at the conducting interface between the two wide-band-gap insulators LaAlO 3 and SrTiO 3 (STO). The profiles are deduced from a thermodynamic model considering a local space charge layer (SCL) originating from charge transfer to the interface region, thus combining electronic and ionic reconstruction mechanisms. We show that the electrical potential confining the two-dimensional electron gas (2DEG) at the interface modifies the equilibrium defect co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
82
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 63 publications
(90 citation statements)
references
References 56 publications
8
82
0
Order By: Relevance
“…The defect structure is inhomogeneous when traversing from regions close to the interface to regions farther away from the interface [13]. This will induce different mean scattering times τ i , leading to different mobilities, μ i ¼ eτ i =m à i , of the various charge carrier populations at low temperatures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The defect structure is inhomogeneous when traversing from regions close to the interface to regions farther away from the interface [13]. This will induce different mean scattering times τ i , leading to different mobilities, μ i ¼ eτ i =m à i , of the various charge carrier populations at low temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…The understanding of these properties and, in particular, the interrelation between ionic defects and electronic or magnetic properties is extensively debated. To this end, it has been shown that gradual ionic defect distributions can cause space charges and inhomogeneous electronic carrier concentrations at oxide interfaces [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…15 However, the temperature of 770 K in our experiments would be remarkably low for the formation of Sr vacancy defects, which are typically only considered at temperatures well above 1000 K due to kinetic limitations in the bulk. 15,20,21 However, due to the localization of the predicted effect at the surface, there would be no need for an ionic movement and hence the formation of V Sr at the surface might be possible even at lower temperatures.…”
Section: -mentioning
confidence: 99%
“…This would freeze out some of the concentrations, leading to an effective charge separation at the surface. 15,20 The lower temperature limit at which the surface defect chemistry of the oxygen and strontium sublattices needs to be considered is already well investigated for acceptor-doped SrTiO 3 . However, it is much more complex for donor-doped SrTiO 3 , due to long equilibration times, secondary phase formation, 22 and the stronger influence of cations as electronic charge compensating species.…”
Section: All Article Content Except Where Otherwise Noted Is Licensmentioning
confidence: 99%
See 1 more Smart Citation